PENDIDIKAN JARAK JAUH SEBAGAI SARANA PERBAIKAN LINGKUNGAN - Lina Warlina; Nuraini Soelaiman; Sri Listyarini (LPPM Universitas Terbuka, 2010)
Environmental issues at this time are very worrying it should be handled. This problem can happen because there is no awareness about problems of environment, and of non existing public education about the environment. Environmental education should be given since childhood, because the moral values received during childhood will not be easily forgotten. Presently, environmental education at the elementary level is ignored, because teachers who have knowledge in the field of environment is limited. Environmental education is very important for all, for that reason the socialization of environmental education is very crucial, especially for decision-makers, the bureaucrats and political elite, or those who can influence other people such as teachers and trainers. One alternative for environmental education is through the open and distance learning system. This system is very potential not only as a self-learning need, but also to enhance educational access. Distance learning system can be used for mass education, providing greater opportunity for people to study whenever they have time and wherever they are.